A Medical Records For Digital Forensics Post- Incident Identification Credential - Hamdi, Nurul (JOURNAL OF INFORMATICS AND COMPUTER SCIENCE, 2015)
Medical is a new field in the rapidly evolving world of computers lately with Banta-news showed that review of crimes in the field of computers and the increasing number of books that explore about digital forensics, so the add reference knowledge for young researchers. With the birth of Information Act Electronic Transaction number 11 of 2008, it is increasingly making these disciplines into the tools to dismantle crime involving computer world, because in general, computer crime is leaving digital traces, hence the need for a computer forensics expert who will secure evidence-called digital or digital evidence. Computer Forensics would require a standard operational procedure in taking digital evidence from being contaminated by the time the data was taken from the digital evidence that are easy to forensic computer expert to perform a system recovery after damage.Â Keywords: Medical Informatics, Digital Evidence, Forensic Disk